Pengaruh Produksi Kelapa Sawit Dan Luas Areal Perkebunan Kelapa Sawit Terhadap Produk Domestik Regional Bruto (PDRB) Sektor Perkebunan Provinsi Aceh - Tera Maliani; Nur Asmita; Reymond Sihombing; Puty Andini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
To analyze the influence of oil palm production and the area of ​​oil palm plantations on the GRDP of Aceh Province in the agricultural sector. The processed results of the F-statistical test above can be seen that the F-statistic is 63.95848, the Prob-Statistic value (0.000000) is smaller than the significance level: 0.05. So the hypothesis testing H1 is accepted and H0 is rejected. This explains that simultaneously the land area (X1) and the amount of production This research uses 10 years of dat.